Annona muricata (KAJIAN PEMANFAATAN DAN BIOAKTIVITASNYA DALAM KESEHATAN) - Marina Silalahi (Husada Mahakam, 2020)
Annona muricata (AM) with the local name soursop is a multifunctional plant that is easily found in the yard which is used as a source of fruit, medicine and shade. In Indonesia in the 2000s, AM leaf was widely used as a cancer drug because it was considered safer and cheaper than synthetic drugs. Various facts show that the use of plants as traditional medicine sometimes causes side effects. This study aims to reveal the relationship between the use of AM as a traditional medicine and its bioactivity. The writing of this article is based on the study of literature in various books, research results and journals published online and offline by using the keywords Annona muricata and Annona muricata bioactivity. In ethnobotany AM is used as a treatment for intestinal worms, cancer, anti-hypertension, diabetes mellitus, headaches, fever, toothache, cough, and asthma. Various research results show that AM bioactivity as anti-Leismania, anti-helmet, anti-cancer, anti-oxidant, antidiabetic mellitus, and anti-malaria. Annonacin, acetogenin, and polyphenols are AM bioactive compounds that are known to have chemopreventive effects on cancer.